ADA HUBUNGAN ANTARA PENGETAHUAN TENTANG HIPERTENSI DENGAN FREKUENSI PEMANFAATAN PELAYANAN KESEHATAN PADA LANSIA - Wahyuni Puji Widiastuti; Endang Purwanti; Sulistyaningsih (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Life expectancy keeps increasing time to time. It will, of course, affect on health conditions, one of which is hypertension disease. Hypertension prevalence is predicted to reach 60% in 2025, which is about 1.56 millions patients with hypertension. This increase is due to people’s low awareness in checking blood pressure early before getting hypertension symptoms. Patients’ lack of knowledge on the signs and symptoms of hypertension results in their ignorance to have regular check-up. Based on the result of health activities of the elderly group in Puskesmas (Community Health Center) Sawangan II, it was found out that the highest number of hypertension patients was in Sawangan. The prevalence of the elderly visitation in 2012 was 573 and about 23% or 101 elder people got hypertension. Objective: To investigate the correlation between knowledge on hypertension and frequency of health service utilization in Sawangan Village, Sawangan, Magelang District Methodology: This study was a non-experimental quantitative study with cross sectional design. Population of this research was elder people in the age of more than 60 years old living in Sawangan, Magelang District who were diagnosed of having hypertension in 2012. Sample of this study was 81 people who lived in 6 villages in Sawangan. Sample was taken using proportioate random sampling. Data were analyzed using Chi-square with α value 0.05. Findings: Fourty-seven people (58%) had good knowledge on hypertension. Fifty-three people (65.4%) had regular health service utilization frequency. Statistically, there was correlation between knowledge on hypertension and frequency of health service utilization in Sawangan Village, Sawangan, Magelang District. The significant value α was 0.000 < α=0.05 Conclusion: There was correlation between knowledge on hypertension and frequency of health service utilization in Sawangan Village, Sawangan, Magelang District. Keywords : Hypertension, Health Service Utilization,Knowledge